Epstein-Barr Virus and COVID-19 Induced Systemic Inflammatory Response Syndrome and Guillain-Barré Syndrome - A Novel Case Report - Chakraborty, Sudipto; Rahaman, Mohidur; Dey, Pradip; Purkait, Siktha; Sengupta, Swagatam; Mandal, Anweshan; Bhaumik, Sanjay; Ramasubban, Suresh (Brazilian Journal of Case Reports, 2025)
A 51-year-old gentleman without any comorbidities was admitted to the hospital with complaints of fever and sore throat. On examination and investigation, he was found to have jaundice and acute kidney injury with biochemical pancreatitis. He was being treated conservatively with IV Fluids and IV Antibiotics. Investigations revealed that he was suffering from the Epstein-Barr virus, and he improved with the ongoing treatment. But on day 5 of admission, he suddenly developed bilateral facial nerve palsy with weakness of the bilateral lower limbs. The nerve conduction velocity test was suggestive of Guillain-Barré syndrome. Incidentally, on the same day, he also tested positive for COVID-19. He was then initiated on IV Immunoglobulin and showed a remarkable response, with improvement in limb power and facial weakness. He was discharged after completing 5 days of IV immunoglobulin treatment for further outpatient care, including continuation of physiotherapy at home.